The RNA Structure of cis-acting Translational Elements of the Chloroplast psbC mRNA in Chlamydomonas reinhardtii - Rahim, Mir Munir A.; Vigneault, Frederic; Zerges, William (Frontiers in Plant Science, 2016)
Photosystem II is the first of two light-driven oxidoreductase complexes in oxygenic photosynthesis. The biogenesis of photosystem II requires the synthesis of polypeptide subunits encoded by the genomes in the chloroplast and the nucleus. In the chloroplast of the green alga Chlamydomonas reinhardtii, the synthesis of each subunit requires interactions between the 5’ UTR of the mRNA encoding it, and gene-specific translation factors. Here, we analyze the sequences and structures in the 5’ UTR of the psbC mRNA, which are known to be required to promote translation and genetic interaction with TBC1, a nuclear gene required specifically for psbC translation. Results of enzymatic probing in vitro and chemical probing in vivo and in vitro support three secondary structures and reveal that one participates in a pseudoknot structure. Analyses of the effects of mutations affecting pseudoknot sequences, by structural mapping and thermal gradient gel electrophoresis, reveal that flexibility at the base of the major stem-loop is required for translation and higher order RNA conformation, and suggest that this conformation is stabilized by TBC1. This RNA pseudoknot tertiary structure is analogous to the internal ribosome entry sites (IRES) that promote translation of certain viruses and cellular mRNAs in the nuclear-cytoplasmic systems of eukaryotes.